(untitled) (UNED Research Journal, 2014)
Morbidity is an important indicator of the causes of mortality in a population, and its study allows focusing preventive health activities. This report presents data on the medical service of a state university in Costa Rica whose participants were the employees who became outpatients from January 19, 2009 to December 14, 2012. I analized 2 010 electronic medical files. The main findings were that 53% of the population had between 1-10 annual consultations, young adults and adults consult in the same proportion. There were weekly and monthly cycles, just like in other health services in Costa Rica. The occupation and socioeconomic status (presented in some other studies as determinants of morbidity) in this population are not different from those in the national population. Many consultations are related to poor hygiene, inadequate diet and a sedentary lifestyle as well as to poor postural hygiene.